ASSESSING THE FEASIBILITY OF MALANG RAYA MOSQUES IN THE RELIGIOUS MODERATION PROGRAM - Rosidin, Rosidin; Handoko, Handoko; Ma'mun, Sukron (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This article aims to assess the feasibility of Malang Raya mosques in the Religious Moderation Program through the perspective of Durkheim, Parsons, and Merton’s functionalist sociological theories. Employing a qualitative approach, the research utilizes a case study methodology across multiple sites, specifically Al-Ghozali Mosque (Islamic education institution area), Al-Mukhlisin Mosque (residential area), and Al-Barokah Mosque (housing area). The findings align with four indicators of religious moderation: First, all three mosques fulfill the National Commitment standards based on empirical data related to organic solidarity that fosters a functional society, as evidenced by the manifest and latent functions exhibited by the mosques in the context of national commitment (Mu’ahadah Wataniyyah) and adherence to laws (Dusturiyyah). Second, the mosques meet the tolerance standards through their affiliations with mass organizations, namely Nahdlatul Ulama and Muhammadiyyah, which have historically demonstrated tolerance (Tasamuh), as well as the principle of justice (‘Adliyyah) upheld through financial transparency and accountability. Third, the mosques satisfy the anti-violence standards through programs promoting care and compassion (Rahamutiyyah) for women, children, the elderly, orphans, and the impoverished, alongside the active involvement of women (Mubadalah) in mosque activities, mainly as educators and staff at Al-Qur’an Learning Centre (Taman Pendidikan Al-Qur’an or TPQ) affiliated with the mosque. Fourth, the mosques adhere to the standards for acceptance of tradition through activities that reflect local traditional values (‘Urfiyyah), such as the mosque's architectural style; humanity (Insaniyyah), exemplified by economic assistance for disaster victims; and public welfare (Maslahah), demonstrated by their concern for the rights of road users.